Fiscal Decentralization, Public Debt Dynamics, and Economic Growth: Empirical Evidence from Selected South Asian Economies - Dr. Mahmood-ul-Hasan; Kiran Saeemab; Haider Ali (Social Science Review Archives, 2025)
Fiscal decentralization, involving the transfer of expenditure and revenue authority to subnational governments, poses risks like excessive subnational borrowing while promising enhanced public service delivery and economic efficiency in diverse South Asia. This study examines the interplay between fiscal decentralization, public debt, and economic growth using panel data from eight South Asian countries (Pakistan, India, Bangladesh, Sri Lanka, Nepal, Bhutan, Maldives, Afghanistan) spanning 1995-2022. Employing robust econometric methods including Pooled Mean Group (PMG), Mean Group (MG), dynamic fixed effects, FMOLS, DOLS, alongside Westerlund and Pedroni cointegration tests the analysis addresses endogeneity and cross-sectional dependence. Key findings reveal expenditure decentralization reduces public debt but exerts mixed effects on growth, with revenue decentralization positively impacting GDP. Public debt consistently hampers growth in both short and long runs, even below 90% GDP thresholds prevalent regionally. Results affirm debt's growth-inhibiting role and advocate revenue decentralization for fiscal discipline. Policy recommendations emphasize institutional strengthening, hard budget constraints, and balanced devolution to sustain 5-7% growth amid crises.